A Criação de Frangos na Fase de 1 a 21 Dias de Idade e a Importância do Ensaio de Desempenho de Frangos de Corte. - Alves, Carla Fonseca (Universidade Federal do Tocantins, 2023)
The objective of this report to monitor the activities developed in the area of poultry Federal University of Tocantins And company North Wing food regarding the initial management, such as: cleaning and disinfection of poultry, management pre-establishment, receipt of chicks, management up to 21 days of age and preparation of pre-research project on technical feasibility of inclusion of gross glycerin, in balanced diets for broilers from 1 to 21 days old. In experiment research will be used 200 broilers of the lineage Coob 500®, was allotted to a completely randomized design with four treatments (0, 2, 4 and 6% inclusion of glycerin) and five replicates and 10 birds per experimental unit. Will be evaluated the performance (feed consumption, weight gain and feed conversion) and meteorological data. The stage was very important to supplement the learning process, giving basis consistent with the activities allowing and improvement in the area of research.